The Implementation of Scientific Approach to Increase Mathematical Problem Solving Ability on Junior High School Students - Siti Nurlelah; Heris Hendriana; Aflich Yusnita Fitrianna (IKIP Siliwangi, 2023)
Mathematics is a field of study that plays an important role in the world of education. Mathematics as a science that must be mastered because it supports and is interelated with other subjects. The background of writing this article is the low ability of students to solve mathematical problems. This research was conducted because there are still many teacher centered learning acitivities.To improve the ability to solve the need for an approach model that an be developed to position students as learning centers is the application of scientific models.the scientific approach is an approach aimed at students. In learning activities direct students to be active and understand the concept. This study aims to apply a scientific approach to Dharma Kartini Junior High School students. The research target was class VIII with a 28 students on the subject matter of a two variable linear equation system. The research conducted was classroom action research.Classroom action research trains critical, systematic thinking, starting from planning, implementing, observing and reflecting. This study provided instruments, namely pre-test and post-test in the form of 5 questions of problem solving abilities to students which were carried out in 2 cycles. The research results obtained for the first cycle showed that students mastery of mathematical concepts was still not good. Therefore, proceed to the next stage, namely the second cycle. Based on the implementation of learning in the second cycle, a very significant increase was obtained. Thus it can be concluded that the scientific approach can be applied in learning to improve problem solving abilities in the matter of a system of two variable linear equations.